1989
DOI: 10.1136/thx.44.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Lung function after coronary artery surgery using the internal mammary artery and the saphenous vein.

Abstract: Lung volumes and arterial blood gas tensions in patients undergoing coronary artery surgery were compared in 77 patients given an internal mammary artery graft (group 1) and 33 patients given a saphenous vein graft only (group 2). Patients in both groups developed a severe restrictive ventilatory defect after surgery, more pronounced in those receiving an internal mammary artery graft. Mean (SEM) vital capacity in groups 1 and 2 was reduced to 36% (1-2%) and 45% (2-0%) of preoperative values on the second post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 6 publications
4
30
0
5
Order By: Relevance
“…The present study demonstrated that, regardless of the sternal incision, there was an evident decrease in the early PO pulmonary function in the off-pump CABG surgery, an inevitable consequence reported by previous studies, which analyzed on-pump procedures [11][12][13][14] .…”
Section: Cms Ms 1 St Postoperative Daymentioning
confidence: 68%
See 2 more Smart Citations
“…The present study demonstrated that, regardless of the sternal incision, there was an evident decrease in the early PO pulmonary function in the off-pump CABG surgery, an inevitable consequence reported by previous studies, which analyzed on-pump procedures [11][12][13][14] .…”
Section: Cms Ms 1 St Postoperative Daymentioning
confidence: 68%
“…Moreover, the use of the LITA, which typically necessitates the insertion of a pleural drain, can be an adjuvant factor for PO pulmonary dysfunction [13][14][15] . …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some reports have found that IMA patients have worse pulmonary functions than the RSVG patients in the postoperative period. 5 Basal atelectasis develops early during anaesthesia and may persist in the postoperative period. After surgery both respiratory muscles weakness and reduced, uncoordinated rib case expansion contribute to the restrictive ventilatory defect following median Sternotomy.…”
Section: Evaluation Of Pulmonary Function After Offpump Coronary Artementioning
confidence: 99%
“…Indeed, some reports have found that IMA patients have worse pulmonary functions than the RSVG patients in the postoperative period. 5 Basal atelectasis develops early during anaesthesia and may persist in the post-operative period. After surgery both respiratory muscles …”
Section: Introductionmentioning
confidence: 99%